TUMOR OBSTRUCTION OF THE INFERIOR VENA CAVA AND ITS TRIBUTARIES: DIAGNOSIS, FEATURES OF SURGICAL INTERVENTIONS, THE RESULTS OF SURGICAL TREATMENT. PART I - G. G. Khubulava; V. A. Tarasov; E. K. Gavrilov; I. A. Larin (Вестник хирургии имени И.И. Грекова)
.